Activation of bombesin receptor Subtype-3 by [D-Tyr6 ,b Ala11,Phe13,Nle14]bombesin6-14 increased glucose uptake and lipogenesis in human and rat adipocytes - Moreno Villegas, Zaida; Martín Duce, Antonio; Aparicio, César; Portal Núñez, Sergio; Sanz, Raúl; Mantey, Samuel A.; Jensen, Robert T.; Lorenzo, Oscar; Egido, Jesús; González, Nieves (My University, 2018)
obese and/or diabetic patients, and BRS-3 KO-mice developed obesity. In this work, focused on rat/hu man adipose tissue, BRS-3 gene-expression was lower than normal-levels in hyperlipidemic, type-2- diabetic (T2D), and type-1-diabetic rats and also in obese (OB) and T2D patients. Moreover, BRS-3 protein levels were decreased in diabetic rat and in obese and diabetic human fat pieces; but neither mutation nor even polymorphism in the BRS-3-gene was found in OB or T2D patients. Interestingly, in rat and human adipocytes, without metabolic alterations, [D-Tyr6 ,b-Ala11,Phe13,Nle14]bombesin6-14 dBRS-3- agonistd, as insulin, enhanced BRS-3 gene/protein expression, increased, PKB, p70s6K, MAPKs and p90RSK1 phosphorylation-levels, and induced a concentration-related stimulation of glucose transport, GLUT-4 membrane translocation and lipogenesis, exclusively mediated by BRS-3, and abolished by wortmannin, PD98059 or rapamacyn. These results confirm that BRS-3 and/or its agonist are a potential therapeutic tool for obesity/diabetes.